Dual-demand pacing for reciprocating atrioventricular tachycardia. Issue 6018 (8th May 1976) - Krikler, D; Curry, P; Buffet, J
Abstract : By using programmed electrical stimulation of the heart and studying the initiation and termination of reciprocating atrioventricular tachycardia two patients with the Wolff-Parkinson-White syndrome were shown to respond rapidly and consistently to fixed-rate pacing. A demand pacemaker was implanted in each patient, having been modified so as to switch into the fixed-rate mode whenever the tachycardia began, thereby terminating the arrhythmia. This appears to be a promising form of treatment in patients with otherwise intractable paroxysmal tachycardia who have been shown by careful study to respond in this way.